The Relationship Between Hand Function and Overlapping Motor Representations of the Hands in the Contralesional Hemisphere in Unilateral Spastic Cerebral Palsy. (January 2018) - Marneweck, Michelle; Kuo, Hsing-Ching; Smorenburg, Ana R. P.; Ferre, Claudio L.; Flamand, Veronique H.; Gupta, Disha; Carmel, Jason B.; Bleyenheuft, Yannick; Gordon, Andrew M.; Friel, Kathleen M.
Background. In many children with unilateral spastic cerebral palsy (USCP), the corticospinal tract to the affected hand atypically originates in the hemisphere ipsilateral to the affected hand. Such ipsilateral connectivity is on average a predictor of poor hand function. However, there is high variability in hand function in these children, which might be explained by the complexity of motor representations of both hands in the contralesional hemisphere. Objective. To measure the link between hand function and the size and excitability of motor representations of both hands, and their overlap, in the contralesional hemisphere of children with USCP. Methods. We used single-pulse transcranial magnetic stimulation to measure the size and excitability of motor representations of both hands, and their overlap, in the contralesional hemisphere of 50 children with USCP. We correlated these measures with manual dexterity of the affected hand, bimanual performance, and mirror movement strength. Results. The main and novel findings were (1) the large overlap in contralesional motor representations of the 2 hands and (2) the moderate positive associations of the size and excitability of such shared-site representations with hand function. Such functional associations were not present for overall size and excitability of representations of the affected hand. Conclusions. Greater relative overlap of the affected hand representation with the less-affected hand representation within the contralesional hemisphere was associated with better hand function. This association suggests that overlapping representations might be adaptively "yoked, " such that cortical control of the child's less-affected hand supports that of the affected hand.